Postexposure management of occupational injuries amongst health care workers - Divya Deodhar; Jency Maria Koshy; Mary John (Wolters Kluwer Medknow Publications, 2016)
Occupational exposure comprises of needle stick injury (NSI) and mucosal splashes. A health care worker (HCW) is at a greater risk of developing blood borne virus infection while at work. Due to high prevalence of human immunodeficiency virus, hepatitis B surface antigen and hepatitis C virus in developing countries, there is a higher risk of infection after occupational exposure to HCW. Factors such as sub-optimal infection control practices and lack of equipment, increases the risk of acquiring NSIs. Reporting of each episode of occupational exposure should be mandatory in institutions. Postexposure management policies should be included among the institutional policies.